2014
DOI: 10.1063/1.4860276
|View full text |Cite
|
Sign up to set email alerts
|

Water and ion transport in ultra-adsorbing porous magnesium carbonate studied by dielectric spectroscopy

Abstract: Porous materials are used in application areas ranging from drug and vaccine delivery, medical implants, molecular sieves and cosmetics to catalysis and humidity control. In the present work, we employed an alternative approach to gain in-depth understanding about water interaction properties in such materials by the use of dielectric spectroscopy and thereby show that it is possible to obtain information that is not accessible from the more commonly employed water interaction analysis techniques. Specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 70 publications
0
21
0
Order By: Relevance
“…A reasonable explanation for the slow-release region could be that the carboxylic groups of the ibuprofen molecules interacted with hydroxyl groups on the Upsalite ® pore wall surface remaining after synthesis. 13 A similar hydrogen bond interaction between the carboxylic group on ibuprofen and silanol groups on the pore walls of mesoporous silica has been hypothesized to cause the experimentally observed plateau in ibuprofen release from mesoporous silica. The slow release of drug from that material extends over several days.…”
Section: Dissolution Profilementioning
confidence: 90%
See 1 more Smart Citation
“…A reasonable explanation for the slow-release region could be that the carboxylic groups of the ibuprofen molecules interacted with hydroxyl groups on the Upsalite ® pore wall surface remaining after synthesis. 13 A similar hydrogen bond interaction between the carboxylic group on ibuprofen and silanol groups on the pore walls of mesoporous silica has been hypothesized to cause the experimentally observed plateau in ibuprofen release from mesoporous silica. The slow release of drug from that material extends over several days.…”
Section: Dissolution Profilementioning
confidence: 90%
“…[7][8][9][10] In our previous work, the novel mesoporous and amorphous material Upsalite ® was investigated as a phase stabilizer of amorphous ibuprofen to increase its dissolution rate. [11][12][13][14] Upsalite ® consists of magnesium carbonate (MgCO 3 ) that is "generally recognized as safe" by the FDA. It has a large specific surface area (typically 300-800 cm 2 /g) and a narrow pore-size distribution (usually 6-8 nm), and these material properties have been associated with high loading of ibuprofen (30%) and suppressed crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…One may expect that such surfactant-free synthesis routes, where calcination at high temperatures is not needed, may be important for the up-scalable production of mesoporous materials. The industrial feasibility of the MMC is further emphasised by the material's moisture sorption properties, [47][48][49][50] biocompatibility 51 and drug stabilising properties. 22,23 Most recently we also showed that MMC has the ability to prevent blood clotting, 52 which opens up its potential for application where blood clotting needs to be suppressed.…”
Section: Introductionmentioning
confidence: 99%
“…As previously concluded, 9 for uncalcined Upsalite the bound proportion of the adsorbed water is high irrespective of sorption route and RH: For very low RHs ∼ 80−90% is bound to the solid and when the RH increases, a somewhat higher proportion is free. At 95% RH ∼ 67% of the adsorbed water is bound.…”
Section: Ds Results As Mentioned In the Introduction Calcinedmentioning
confidence: 61%
“…9 DS measures the dielectric properties of matter through its response to an applied electric field in a broad frequency range (10 −6 −10 11 Hz). A sinusoidal ac voltage is applied across the sample localized between two electrodes and the current response (amplitude and phase) is measured while the angular frequency ω = 2πf of the voltage is varied.…”
Section: Introductionmentioning
confidence: 99%